Creation as divine absence: A metaphysical reframing of the problem of evil - Fritts, Megan (Religious studies, 2026)
The philosophical ‘problem of evil’ goes back at least as far as Epicurus and has remained a powerful argument against the existence of God in contemporary philosophy. The argument is rooted in apparent contradictions between God’s divine attributes and various conditions of human existence. But these contradictions arise only given certain assumptions of what we should expect both God and the world to be like given God’s existence. In this article, I argue that we can utilise the work of the twentieth-century French philosopher Simone Weil to craft a coherent metaphysical picture of God, creation, and suffering that rejects these common assumptions. Further, I contend that this picture very plausibly follows from commonly accepted tenets of traditional monotheism. Given this, I argue that this Weil-inspired framework provides serious reasons for reframing the problem of evil and its corresponding theodicies by presenting a radically different view of how God must relate to creation. Yet, this picture does not necessarily vindicate the theist. I argue that this picture may leave us with a new question about creation in the face of evil. Namely, is it possible to understand God’s initial creative act as Weil describes it - as an act of love?